Mixed Marriages at the Eucharist: Canon 1120 - Huels, John M. (Roman replies and CLSA advisory opinions 1996, 1996)
In your book, The Catechumenate and the Law (Chicago: Liturgy Training Publications, 1995), you state that it is forbidden to celebrate a marriage between a Catholic and a non-baptized person, including a catechumen, at the Eucharist. What is the legal basis for this statement? Is it only because there is a special rite for this kind of marriage? May a Catholic marry a Mormon at the Eucharist?